Sistem Informasi Manajemen Keuangan Berbasis Web untuk Meningkatkan Transparansi Pengelolaan Kas RT - Sutrisno, Sutrisno; Lestari, Tri Putri; Sari, Atalya Kurnia; Hidayat, Manarul (Universitas Indraprasta PGRI Jakarta, 2025)
Manual financial management at the neighborhood association (RT) level often results in data disorder, miscommunication, and low transparency and citizen participation. In the digital era, a web-based financial information system is an important solution for realizing effective and accountable fund management. This study aims to implement a web-based financial management information system to improve RT cash transparency at Meadow Green Residence 3, Depok. This study uses a qualitative approach with a grounded research method, through field observations, interviews, and literature studies. The COBIT 2019 framework is applied as a reference in designing system governance. The system is designed using UML and ERD diagrams, then implemented into a web interface. Testing is carried out using the black box testing method. The results show that the system runs according to design, all features such as login, transaction input, reports, and printing of reporting periods function properly. This system is able to improve the efficiency, transparency, and accountability of RT financial management, and is suitable for implementation in similar communities.